Pemanfaatan Media Inovatif “Periscope Grid” Berbasis Hybrid Learning dalam Pembelajaran Gambar Dua Dimensi di Sekolah Dasar - Ferdianto, Ari; Eka Titi Andaryani; Deni Setiawan (Universitas Palangka Raya, 2025)
This study aims to describe the use of the innovative Periscope Grid media based on hybrid learning in two-dimensional drawing lessons for elementary students. The media was designed to help students understand perspective and proportion concepts by combining a manual transparent grid frame with digital features accessed through QR codes linked to tutorial videos, artwork galleries, and reflective learning materials. The research employed a descriptive qualitative approach involving fourth-grade elementary students. Data were collected through classroom observations, interviews with teachers and students, and documentation of students’ artwork. The data were analyzed interactively using reduction, presentation, and conclusion drawing stages. The findings reveal that the Periscope Grid effectively enhances students’ ability to observe, replicate, and draw proportional two-dimensional objects while promoting collaboration through digital gallery activities. Moreover, the media helps teachers explain perspective concepts more easily and fosters students’ active participation. It can be concluded that Periscope Grid serves as an effective, engaging, and integrative learning medium suitable for 21st-century visual art education in elementary schools.